2019
DOI: 10.21776/ub.jam.2019.017.03.12
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Success Factors Implementation of State Civil Apparatus Management Information System

Abstract: The State Civil Apparatus Management Information System, commonly called as SIM ASN, is used to manage staff data that contains all information about the State Civil Apparatus at the Ministry of Agriculture. This study aims to analyze the factors that influence the success of SIM ASN, in accordance with DeLone and McLean's information system success model (2003). Specifically, the purpose of this study is to analyze the effect of information quality,system quality, and service quality on use and user satisfact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
0
0
1
Order By: Relevance
“…Kualitas sistem memberikan pengaruh positif dan signifikan terhadap kepuasan pengguna dengan nilai koefisien beta 0.257 dan t-statistik 3.621. Hasil ini didukung oleh penelitian Nauli (2015), Tajuddin (2015), Arsyanur et al (2019) Penggunaan memberikan pengaruh positif dan signifikan terhadap kepuasan pengguna dengan nilai koefisien beta 0.180 dan t-statistik 3.388. Hasil ini mendukung penelitian sebelumnya diantaranya penelitian Rahmat et al (2019) dan Bokhari (2005).…”
Section: Nilaiunclassified
“…Kualitas sistem memberikan pengaruh positif dan signifikan terhadap kepuasan pengguna dengan nilai koefisien beta 0.257 dan t-statistik 3.621. Hasil ini didukung oleh penelitian Nauli (2015), Tajuddin (2015), Arsyanur et al (2019) Penggunaan memberikan pengaruh positif dan signifikan terhadap kepuasan pengguna dengan nilai koefisien beta 0.180 dan t-statistik 3.388. Hasil ini mendukung penelitian sebelumnya diantaranya penelitian Rahmat et al (2019) dan Bokhari (2005).…”
Section: Nilaiunclassified
“…Ini mencerminkan sejauh mana harapan, kebutuhan, dan keinginan pengguna telah terpenuhi atau terlampaui. Kepuasan pengguna merupakan indi-kator penting dari kualitas dan keberhasilan suatu produk atau layanan (Asyanur et al, 2019). Indikator-indikator yang membentuk user satisfaction di antaranya adalah Overall satisfaction, Information satisfaction, dan Feature satisfaction (Sulaiman et al, 2023).…”
Section: User Satisfactionunclassified
“…The research results show that information quality has a positive effect on perceived ease of use (Machdar, 2016), system and information quality or ISSM dimensions have an effect on the use of e-learning systems (Purwanto and Pawirosumarto, 2017), and perceptions of usefulness (Tiana et al, 2019), perceived ease of use (Rezvani et al, 2022), and ease of use (Martono et al, 2020). Ease of use influences the success of the ASN SIM at Ministry of Agriculture (Arsyanur et al, 2019). However, Krisdiantoro et al (2019), Khairrunnisa and Yunanto (2017), and Wahyudi et al (2017) found that the ISSM dimensions did not affect the implementation of e-procurement systems.…”
Section: Introductionmentioning
confidence: 98%